Laser 40 Ar/ 39 Ar thermochronology of Archean rocks in Yellowknife Domain, southwestern Slave Province: insights into the cooling history of an Archean granite-greenstone terrane - Bethune, Kathryn M; Villeneuve, Michael E; Bleeker, Wouter (Canadian Journal of Earth Sciences, 1999)
Laser 40 Ar/ 39 Ar ages for hornblende, muscovite, and biotite from Archean plutonic rocks of Yellowknife Domain, southwestern Slave Province, complement U-Pb ages from minerals with higher closure temperatures (zircon, monazite, titanite). Together, the data indicate that the plutonic suites of different ages (Defeat, Prosperous, Morose) coring three major thermal culminations in the domain have distinct Archean cooling histories until below approximately 250°C (biotite closure). The cooling trajectories for successive suites appear to document a decrease in cooling rate over the course of orogeny, possibly reflecting the build-up of heat within the orogen, coupled with a transition to lower rates of exhumation and (or) erosion. Greater structural relief over the Sleepy Dragon basement culmination may be responsible for slower cooling of the Morose Granite situated in its core. At or below the closure temperature of biotite the cooling curves converge with one another, documenting a transition from "localized" to "regional" cooling. The fact that cooling was locality specific until at least the biotite closure temperature suggests that, just as intrusion and related peak metamorphism were diachronous across the region, so was cooling to approximately 250°C. Uniform regional isotherms thus were not established until >200 Ma after the youngest Archean plutonism. The variable disturbance of biotite Ar spectra, but generally not muscovite or hornblende, indicates that the Paleoproterozoic thermal disturbance of Archean rocks in Yellowknife Domain did not exceed 200-300°C.